Electrical characterization and device characterization of ZnO microring shaped films by sol-gel method - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
Zinc oxide microrings formed nanoparticles were prepared on n-type silicon substrate by sol-gel method. The structure of ZnO film is confirmed by XRD analysis and ZnO film exhibits a polycrystalline grown with a hexagonal wurtzite-type. The optical band gap of the ZnO film deposited on silicon substrate was determined using the reflectance spectra by means of Kubelka-Munk formula and was found to be 3.22 eV. The structural properties of the ZnO film were investigated by atomic force microscopy. The AFM results indicate that the ZnO film is consisted of microrings with nanoparticles. A single phase of ZnO microring with outer diameter is ranging from 2.2 mu m to 1.72 mu m and inner diameters ranging from 125 nm to 470 nm was obtained. A Schottky diode having Au/n-type ZnO plus n-type silicon structure was fabricated. The current-voltage and impedance spectroscopy properties of the diode have been investigated. The barrier height phi(b) and ideality factor n values for the diode were found to be 0.80 eV and 2.01, respectively. The series resistance for the diode was calculated from the admittance behavior in accumulation region. The interface state density profile for the diode was obtained. The obtained results indicate that the electric parameters of the diode are affected by structural properties of ZnO film. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: ZnO; Sol-gel; Nanoparticles; Schottky diode